Thinking action as a performative and participative mental awareness - Ziegler, Renatus; Weger, Ulrich (Frontiers in Psychology, 2023)
This paper seeks to evaluate experiential facets of thinking action using first-person phenomenological methods. We begin our considerations using a simple mathematical proof as a case study – and also employ phenomenological contrasts between different types of thinking. They reveal that thinking actions produce performative insights rather than dispositional or remembered knowledge. This distinction allows us to introduce a new mode of thinking that is different from most known types of thinking, namely pure thinking action. The performative nature of this pure thinking action is participative and receptive with respect to concepts and has the quality of being persistent and coherent during its episode of action. Moreover, it is the often unattended source of thinking everyday life.